Composition for preventing skin aging
Patent Information
- Application Number
- JP2020118576
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-09
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2040-07-09
AI Technical Summary
【0008】 本発明によれば、従来よりも、皮膚のシワや、皮膚のハリ等を改善することが可能な、皮膚の老化防止用組成物を提供することが可能になる。
Smart Images

Figure 0007651153000012 
Figure 0007651153000013 
Figure 0007651153000014
Abstract
Description
[Technical field]
[0001] The present invention is a method for preventing skin aging. Assembling Related to the composition. [Background technology]
[0002] 2. Description of the Related Art With the increasing awareness of beauty in modern times, various anti-aging cosmetics that improve wrinkles, skin firmness, and the like have been proposed. As such an anti-aging cosmetic, for example, hibiscus extract is disclosed in Patent Document 1. It is believed that hibiscus extract may activate the proliferation of fibroblasts and improve skin wrinkles, skin firmness, and the like. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-295928 Summary of the Invention [Problem to be solved by the invention]
[0004] Simply activating the proliferation of fibroblasts may not be enough to sufficiently improve skin wrinkles, skin firmness, and the like.
[0005] The present invention has been made in consideration of the above problems, and aims to provide a composition for preventing skin aging that is capable of improving skin wrinkles, skin firmness, and the like more than conventional compositions. [Means for solving the problem]
[0006] In order to achieve the above object, the present invention provides a method for preventing skin aging. stop use The composition comprises: Contains silicon and a pH adjuster, The silicon content is 0.05% by mass or more and less than 100% by mass, The silicon is water-soluble silicon extracted from quartz, Improves skin wrinkles and firmness For Used, It is used by applying it to the skin.
[0007] For example, the silicon content is 0.05 mass% or more. 5.0 It may be less than % by mass. Effect of the Invention
[0008] According to the present invention, it is possible to provide a composition for preventing skin aging that can improve skin wrinkles, skin firmness, and the like more effectively than ever before. [Brief description of the drawings]
[0009] [Figure 1] 1 is a graph showing the elastase inhibitory activity of silicon. [Diagram 2] (a) is a graph showing the effect of silicon on wrinkles, and (b) is an image of wrinkles on a replica. [Diagram 3] 1 is a graph showing the effect of silicon on water loss from the skin. [Figure 4] 1 is a graph showing the effect of silicon on hyaluronic acid production. [Diagram 5] 1 is a graph showing the effect of silicon on the expression of collagen degrading enzyme 1 gene (MMP1). [Figure 6] 1 is a graph showing the effect of silicon on the expression of hyaluronic acid synthase 2 gene (HAS2). [Figure 7] 1 is a graph showing the effect of silicon on the expression of hyaluronic acid synthase 3 gene (HAS3). [Figure 8] 1 is a graph showing the effect of silicon on the expression of the β-glucocerebrosidase gene (GBA). [Figure 9] 1 is a graph showing the effect of silicon on the expression of the profilaggrin gene (FLG). [Figure 10]1 is a graph showing the effect of silicon on the expression of tranglutaminase 1 gene (TGM1). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The composition for preventing skin aging according to an embodiment of the present invention will be described below.
[0011] The composition for preventing skin aging of the present invention contains silicon.
[0012] The silicon is amorphous silicon, and examples of the silicon include silicon derived from food and silicon derived from minerals. Examples of dietary silicon include silicon contained in grains, vegetables, seaweed, etc. Examples of grains include wheat, brown rice, white rice, and corn. Examples of vegetables include burdock, radish, and carrot. Examples of seaweed include kelp and wakame. Foods such as grains, vegetables, and seaweed may be contained in a pulverized state in the composition for preventing skin aging of the present invention.
[0013] Examples of silicon derived from minerals include silicon extracted from quartz.
[0014] The silicon may be commercially available silicon, for example, silicon contained in the water-soluble silicon "umo (registered trademark)" sold by APA Corporation.
[0015] Furthermore, silicon may be elemental silicon or may be silicon in a compound such as silicon dioxide.
[0016] The content of silicon based on the total weight of the composition for preventing skin aging of the present invention is not less than 0.005% by mass and less than 100% by mass. Furthermore, it is believed that when the composition for preventing skin aging of the present invention is applied to human skin or ingested by humans, it is absorbed through the skin and intestinal tract, improving wrinkles, firmness, and the like of the skin.
[0017] Specifically, when absorbed through the skin or intestinal tract, the skin anti-aging composition of the present invention is believed to have the effect of reducing elastase activity, increasing hyaluronic acid production, and inhibiting collagen degradation, as described in the examples below. Here, these actions are actions to improve wrinkles, firmness, etc. of the skin, but the action of conventional hibiscus extracts to simply activate the proliferation of fibroblasts is thought to merely suggest the possibility of improving wrinkles, firmness, etc. of the skin. Therefore, it is believed that the composition for preventing skin aging of the present invention is more capable of improving skin wrinkles and skin firmness than conventional hibiscus extracts. The composition for preventing skin aging of the present invention improves wrinkles and firmness of human skin, and also has bacteriostatic properties against Escherichia coli and Legionella pneumophila, as will be described in the following examples.
[0018] The content of silicon based on the total mass of the composition for preventing skin aging of the present invention is preferably 0.05% by mass or more and less than 100% by mass. This is believed to make it possible to further improve wrinkles and firmness of the skin when the composition for preventing skin aging of the present invention is applied to human skin or ingested by a human. The silicon content based on the total mass of the composition for preventing skin aging of the present invention is preferably 0.05 mass% or more and less than 100 mass%, and includes, for example, 0.1 mass%, 0.5 mass%, 1.0 mass%, 5.0 mass%, 10 mass%, 15 mass%, 20 mass%, 25 mass%, 30 mass%, 35 mass%, 40 mass%, 45 mass%, 50 mass%, 55 mass%, 60 mass%, 65 mass%, 70 mass%, 75 mass%, 80 mass%, 85 mass%, 90 mass%, and 95 mass%.
[0019] The present invention is not limited to the above-described embodiment, but can be modified and applied in various ways.
[0020] For example, the composition for preventing skin aging of the present invention may contain a component that exhibits an antioxidant effect for improving wrinkles, firmness, and the like of the skin, if necessary. Examples of components that have such antioxidant effects include, but are not limited to, gamma-oryzanol, alpha-lipoic acid, catechins, flavonoids, coenzyme Q10, vitamin C, vitamin E, alpha-carotene, beta-carotene, Enzogenol, royal jelly, uric acid, and citric acid. The composition for preventing skin aging of the present invention may contain at least one of these components exhibiting antioxidant activity, if necessary.
[0021] Furthermore, when the composition for preventing skin aging of the present invention contains the above-mentioned gamma-oryzanol, alpha-lipoic acid, catechins, flavonoids, coenzyme Q10, vitamin C, vitamin E, alpha-carotene, beta-carotene, Enzogenol, royal jelly, uric acid, citric acid, etc., the amount of each of these ingredients is not particularly limited.
[0022] Furthermore, the composition for preventing skin aging of the present invention may contain excipients, pH adjusters, cooling agents, suspending agents, coating agents, colorants, binders, lubricants, surfactants, etc., as necessary.
[0023] Furthermore, the composition for preventing skin aging of the present invention may be contained in a medicine or a food or drink.
[0024] When contained in a pharmaceutical product, it is administered to the human body in the form of, but is not limited to, a tablet, capsule, liquid, powder, paste, gel, or the like together with a pharma- ceutical acceptable carrier.
[0025] Food and beverages refer to beverages or food products, and include, but are not limited to, examples of such products include fruit juice drinks, soft drinks, coffee, vegetable juice, tea, coffee, syrup, vinegar, miso, fruits, vegetables, grains, meat, dairy products, sweets, noodles, jellies, nutritional supplements, functional foods, and health foods.
[0026] Next, the composition for preventing skin aging of the present invention will be described with reference to examples. In the following examples, the silicon contained in the skin aging prevention composition of the present invention was that contained in the water-soluble silicon "umo (registered trademark)" sold by APA Corporation.
[0027] [Elastase inhibitory activity of silicon] Example 1 First, ultrapure water (CAS No. 7732-18-5, Wako, Japan) was added to and mixed with water-soluble silicon "umo" to prepare a test substance with a water-soluble silicon "umo" concentration of 3 mass% just before use. Next, 50 μL of 1.25 μg / mL elastase enzyme (CAS No. 39445-21-1, Sigma-Aldrich, USA) solution and 100 μL of N-Succinyl-Ala-Ala-Ala-p-Nitroanilide (CAS No. 52299-14-6, Sigma-Aldrich, USA) solution were added to the 96-well plate containing 50 μL of the test substance, and the plate was shaken at 270 rpm for 30 seconds and then incubated at 37° C. for 15 minutes. The 96-well plate was then shaken at 270 rpm for 10 seconds to uniformly disperse the dye in the wells, and the absorbance at 415 nm (OD ) was measured using a microplate reader. 415 ) was measured. This absorbance (OD 415 The method for calculating the elastase inhibitory activity of silicon using this will be described later.
[0028] Example 2 The absorbance (OD ) was measured in the same manner as in Example 1, except that the test substance, which had a concentration of water-soluble silicon "umo" of 30% by mass, was prepared just before use. 415 ) was measured.
[0029] Example 3 The absorbance (OD ) was measured in the same manner as in Example 1, except that ultrapure water was not added to the water-soluble silicon "umo". 415) was measured. The test substance in this example was water-soluble silicon "umo" with a concentration of 100%.
[0030] Comparative Example 1 The absorbance (OD ) was measured in the same manner as in Example 1, except that ultrapure water was used as is, without using water-soluble silicon "umo". 415 ) was measured. Note that this comparative example was a control experiment, and ultrapure water was used as the control.
[0031] The absorbance (OD 415 ) was used to calculate the elastase activity of each of the silicon particles in Examples 1 to 3 according to the following formula. Elastase activity rate (%) = (S-SB) x 100 / (C-CB) Here, S is the absorbance of the test substance measured in Examples 1 to 3, SB is the absorbance of the blank of the test substance in Examples 1 to 3, C is the absorbance of the control measured in Comparative Example 1, and CB is the absorbance of the blank control in Comparative Example 1. In the blank, 0.05 M Tris-HCl buffer was used instead of elastase enzyme.
[0032] [The effect of silicon on wrinkles] Example 4 After applying the water-soluble silicon "umo" to the skin replica, the area of wrinkles on the skin replica was measured.
[0033] Comparative Example 2 The wrinkle area of the skin replica was measured before and after applying the water-soluble silicon "umo" to the skin replica.
[0034] [Effect of silicon on water loss from skin] Example 5 First, the amount of water lost from human skin was measured. Next, the water-soluble silicon "umo" was applied to human skin, and the amount of water lost from the skin was measured 30 minutes, 1 hour, and 2 hours later.
[0035] Comparative Example 3 First, the amount of water lost from human skin was measured. Next, without applying the water-soluble silicon "umo" to human skin, the amount of water evaporation from the skin was measured 30 minutes, 1 hour, and 2 hours later.
[0036] [The effect of silicon on hyaluronic acid production] Example 6 Water-soluble silicon "umo" was added to distilled water and mixed to prepare an aqueous solution with a concentration of water-soluble silicon "umo" of 0.01% by mass. This aqueous solution was then added to a medium containing fibroblasts, and the production rate of hyaluronic acid was measured. This measurement was performed three times.
[0037] Example 7 The production rate of hyaluronic acid was measured in the same manner as in Example 6, except that an aqueous solution containing water-soluble silicon "umo" at a concentration of 0.1% by mass was prepared.
[0038] Example 8 The production rate of hyaluronic acid was measured in the same manner as in Example 6, except that an aqueous solution containing water-soluble silicon "umo" at a concentration of 1% by mass was prepared.
[0039] Comparative Example 4 The production rate of hyaluronic acid was measured in the same manner as in Example 6, except that distilled water was added to the medium containing fibroblasts without adding water-soluble silicon "umo". This measurement was used as a control.
[0040] [Effect of silicon on the expression of collagen degrading enzyme 1 gene (MMP1)] Example 9 First, water-soluble silicon "umo" was added to purified water and mixed to prepare a test substance with a water-soluble silicon "umo" concentration of 1% by mass just before use. Next, 5.0 × 10 5 NB1RGB cells (RIKEN BRC, Japan) were seeded at 200 cells / mL and incubated with CO 2 Incubator (CO 2The cells were cultured for 24 hours in a CO atmosphere (5% CO concentration, 37°C). After that, the medium was removed, and the medium containing the test substance prepared just before use was added. 2 The cells were cultured in an incubator for 24 hours.
[0041] Then, RNA extraction and purification was carried out as described below using PureLink (registered trademark) RNA Mini Kit (Cat No. 12183018A, Invitrogen, USA). Specifically, the medium after 24 hours of culture was removed, and the 35 mm dish was washed twice with 2 mL of PBS warmed to 37° C. Then, 600 μL of lysis buffer containing 2 M dithiothreitol (CAS No. 27565-41-9, Invitrogen, USA) was added to dissolve the cells, and the lysate was collected. Then, the cells present in the lysate were disrupted using a Homogenizer (Cat No. 12183-026, Invitrogen, USA). Then, 600 μL of 70% ethanol (CAS No. 64-17-5, Japan alcohol, Japan) solution was added to the cell lysate, which was then transferred to a column with a silica membrane, and centrifuged at 12,000×g at room temperature for 1 second, and the filtrate was discarded. Then, 700 μL of guanidine isothiocyanate-containing Wash Buffer I and 500 μL of ethanol-containing Wash Buffer II were added to the silica membrane to wash it. Then, the mixture was centrifuged at 12,000×g at room temperature for 15 seconds and then dried. Then, 30 μL of RNase-free water was added, the mixture was left to stand at room temperature for 1 minute, and centrifuged at 12000×g and room temperature for 15 seconds. This procedure was repeated twice to elute RNA from the silica membrane. A portion of the RNA was then dispensed into a UV-transparent 96-well plate (Cat No. 8404, Thermo Scientific, USA) and diluted 25-fold with Tris-EDTA Buffer (TE (pH 8.0), Cat No. 310-90023, NIPPON GENE, Japan). The optical density (OD) was measured at 230 nm, 260 nm, and 280 nm using a microplate reader (SPARK® 10M TECAN, Switzerland). 230 ,OD 260 and O.D. 280 ) was measured. The RNA concentration of the test substance was then calculated using the following formula, and diluted with TE Buffer to adjust the RNA concentration to 10 μg / mL. RNA concentration (μg / mL) = A × K × 0.3 × 10 (dilution factor) where A is the OD of the test substance 260 where K=40 (extinction coefficient of RNA) and 1=0.3 (path length (cm)).
[0042] Next, RNA was reverse transcribed using SuperScriptTM IV VILOTM Master Mix with ezDNase (Cat No. 11766050, Invitrogen, USA). Specifically, 1 μL of 10× ezDNase Buffer, 1 μL of ezDNase enzyme, 6 μL of nuclease-free water, and 2 μL of 10 μg / mL RNA were added per well to an 8-tube array (AB1182, Thermo Scientific, USA), and the tubes were incubated at 37° C. for 2 minutes. After 2 minutes, 4 μL of SuperScript™ IV VILO™ Master Mix and 6 μL of Nuclease-free Water were added per well to each of the 8-tube array, and cDNA was synthesized by heating at 25°C for 10 minutes, at 50°C for 10 minutes, and at 85°C for 5 minutes using a real-time PCR system (QuantStudio® 3, Applied Biosystems, USA). Then, 10 μL TaqMan® Fast Advanced Master Mix (Cat No. 4444557, Applied Biosystems, USA), 1 μL Taqman Gene Expressior, 7 μL UltraPure™ Distilled Water (Invitrogen, Cat No. 10977-15, USA) and 2 μL cDNA were added per well to a PCR plate (Cat No. 8010560, Thermo Scientific, USA), and the plate was sealed with a plate seal (Cat No. 4360954, Thermo Scientific, USA). The solution was then spun down in a plate centrifuge to remove any bubbles. Real-Time qPCR was then performed using a real-time PCR system, and the threshold cycle (Ct) value, which is the cycle number when the fluorescent signal of each gene in the test substance reaches an arbitrary threshold, was calculated. The Ct value was then corrected using the internal standard gene to obtain the ΔCt value. The ΔCt value was then corrected using the average ΔCt value of the control, which will be described later, to obtain the ΔΔCt value. Assuming that the difference in detection per cycle due to ΔΔCt is a difference of two-fold, -ΔΔCt The gene expression level of the test substance (MMP1) was calculated by substituting the above and setting the gene expression level of the control as 1. The gene expression level of the test substance (MMP1) was tested for significance using a paired t-test. All tests were two-sided and the significance level was set at less than 5% (P<0.05, P<0.01, P<0.001).
[0043] Example 10 The expression level of MMP1 was measured in the same manner as in Example 9, except that the test substance, which had a concentration of water-soluble silicon "umo" of 3 mass %, was prepared immediately before use.
[0044] Comparative Example 5 The ΔCt value was measured in the same manner as in Example 9, except that the water-soluble silicon "umo" was not added. This measurement value was used as a control. In other words, this comparative example was a control experiment, and purified water was used as the control.
[0045] [Effect of silicon on the expression of hyaluronic acid synthase 2 gene (HAS2)] Example 11 The same procedure as in Example 9 was carried out to measure the expression level of HAS2.
[0046] Example 12 The expression level of HAS2 was measured in the same manner as in Example 11, except that an aqueous solution containing water-soluble silicon "umo" at a concentration of 3 mass % was prepared just before use.
[0047] (Example 13) The expression level of HAS2 was measured in the same manner as in Example 11, except that an aqueous solution containing water-soluble silicon "umo" at a concentration of 10 mass % was prepared just before use.
[0048] Comparative Example 6 The ΔCt value was measured in the same manner as in Example 11, except that the water-soluble silicon "umo" was not added. This measurement value was used as a control. In other words, this comparative example was a control experiment, and purified water was used as a control.
[0049] [Effect of silicon on the expression of hyaluronic acid synthase 3 gene (HAS3)] Example 14 First, water-soluble silicon "umo" was added to purified water and mixed to prepare a test substance with a water-soluble silicon "umo" concentration of 1% by mass just before use. Next, 1.5 × 10 5 HaCaT cells were seeded at 1000 cells / 2 mL and incubated with CO 2 Incubator (CO 2 The cells were cultured for 24 hours in a CO atmosphere (5% CO concentration, 37°C). After that, the medium was removed, and the medium containing the test substance prepared just before use was added. 2 The cells were cultured in an incubator for 24 hours.
[0050] Then, RNA was extracted and purified using PureLink (registered trademark) RNA Mini Kit (Cat No. 12183018A, Invitrogen, USA). Specifically, the medium after 24 hours of culture was removed, and the 35 mm dish was washed three times with 2 mL of PBS preheated to 37° C. Then, 600 μL of lysis buffer containing 2 M dithiothreitol (CAS No. 27565-41-9, Invitrogen, USA) was added to dissolve the cells, and the lysate was collected. Then, the cells present in the lysate were disrupted using a Homogenizer (Cat No. 12183-026, Invitrogen, USA). Then, 600 μL of 70% ethanol (CAS No. 64-17-5, Japan alcohol, Japan) solution was added to the cell lysate, which was then transferred to a column with a silica membrane, and centrifuged at 12,000×g and room temperature for 15 seconds, after which the filtrate was discarded. Then, 700 μL of guanidine isothiocyanate-containing Wash Buffer I and 500 μL of ethanol-containing Wash Buffer II were added to the silica membrane to wash it. Then, the mixture was centrifuged at 12,000×g at room temperature for 15 seconds and then dried. Then, 30 μL of RNase-free water was added, and the mixture was left to stand at room temperature for 1 minute, and then centrifuged at 12,000×g at room temperature for 15 seconds. This procedure was repeated twice to elute RNA from the silica membrane. A portion of the RNA was then dispensed into a UV-transparent 96-well plate (Cat No. 8404, Thermo Scientific, USA), diluted 10-fold with Tris-EDTA Buffer (TE (pH 8.0), Cat No. 310-90023, NIPPON GENE, Japan), and the absorbance (OD) at 230 nm, 260 nm, and 280 nm was measured using a microplate reader (SPARK® 10M TECAN, Switzerland). 230 ,OD 260 and O.D. 280 ) was measured. O.D. 260The RNA concentration of the test substance was calculated using the following formula, and the substance was diluted with TE Buffer to adjust the RNA concentration to 10 μg / mL. RNA concentration (μg / mL) = A × K × 0.3 × 10 (dilution factor) where A is the OD of the test substance 260 where K=40 (extinction coefficient of RNA) and 1=0.3 (path length (cm)).
[0051] Next, RNA was reverse transcribed using SuperScriptTM IV VILOTM Master Mix with ezDNase (Cat No. 11766050, Invitrogen, USA). Specifically, 1 μL of 10×ezDNase Buffer, 1 μL of ezDNase enzyme, 6 μL of nuclease-free water, and 2 μL of 10 μg / mL RNA were added per well to an 8-tube strip (AB1182, Thermo Scientific, USA), and incubated at 37° C. for 2 minutes. After 2 minutes, 4 μL of SuperScript™ IV VILO™ Master Mix and 6 μL of Nuclease-free Water were added per well to each of the 8-tube array, and the mixture was heated at 25°C for 10 minutes, 50°C for 10 minutes, and 85°C for 5 minutes in a real-time PCR system (QuantStudio® 3, Applied Biosystems, USA) to synthesize cDNA. Then, 10 μL TaqMan® Fast Advanced Master Mix (Cat No. 4444557, Applied Biosystems, USA), 1 μL Taqman Gene Expressior, 7 μL UltraPure™ Distilled Water (Invitrogen, Cat No. 10977-15, USA) and 2 μL cDNA were added per well to a PCR plate (Cat No. 8010560, Thermo Scientific, USA), and the plate was sealed with a plate seal (Cat No. 4360954, Thermo Scientific, USA). The solution was then spun down in a plate centrifuge to remove any bubbles. Real-Time qPCR was then performed using a real-time PCR system to calculate the threshold cycle (Ct) value, which is the cycle number when the fluorescent signal of each gene in the test substance reaches an arbitrary threshold. The Ct value was then corrected using the internal standard gene, and this was taken as the ΔCt value. The ΔCt value was corrected using the average ΔCt value of the control, which will be described later, and this was taken as the ΔΔCt value. Assuming that the difference in detection per cycle due to ΔΔCt is a difference of two-fold, 2 -ΔΔCt The gene (HAS3) expression level of the test substance was calculated by assuming the control gene expression level as 1. The gene (HAS3) expression levels of the test substance were tested for significance using a paired t-test. All tests were two-sided and the significance level was set at less than 5% (P<0.05, P<0.01, P<0.001).
[0052] Example 15 The expression level of HAS3 was measured in the same manner as in Example 14, except that the test substance, which had a concentration of water-soluble silicon "umo" of 3 mass %, was prepared immediately before use.
[0053] Example 16 The expression level of HAS3 was measured in the same manner as in Example 14, except that the test substance, which had a concentration of water-soluble silicon "umo" of 10 mass %, was prepared immediately before use.
[0054] Comparative Example 7 The ΔCt value was measured in the same manner as in Example 14, except that the water-soluble silicon "umo" was not added. This measurement value was used as a control. In other words, this comparative example was a control experiment, and purified water was used as a control.
[0055] [Effect of silicon on the expression of β-glucocerebrosidase gene (GBA)] (Example 17) The same procedure as in Example 14 was carried out to measure the expression level of GBA.
[0056] (Example 18) The expression level of GBA was measured in the same manner as in Example 17, except that the test substance, which had a concentration of water-soluble silicon "umo" of 3 mass%, was prepared just before use.
[0057] (Example 19) The expression level of GBA was measured in the same manner as in Example 17, except that the test substance having a concentration of water-soluble silicon "umo" of 10 mass% was prepared just before use.
[0058] Comparative Example 8 The ΔCt value was measured in the same manner as in Example 17, except that the water-soluble silicon "umo" was not added. This measurement value was used as a control. In other words, this comparative example was a control experiment, and purified water was used as a control.
[0059] [Effect of silicon on the expression of the profilaggrin gene (FLG)] (Example 20) The same procedure as in Example 14 was carried out to measure the expression level of FLG.
[0060] Example 21 The expression level of FLG was measured in the same manner as in Example 20, except that the test substance, which had a concentration of water-soluble silicon "umo" of 3 mass %, was prepared immediately before use.
[0061] Comparative Example 9 The ΔCt value was measured in the same manner as in Example 20, except that the water-soluble silicon "umo" was not added. This measurement value was used as a control. In other words, this comparative example was a control experiment, and purified water was used as a control.
[0062] [Effect of silicon on the expression of tranglutaminase 1 gene (TGM1)] Example 22 The same procedure as in Example 14 was carried out to measure the expression level of TGM1.
[0063] Comparative Example 10 The ΔCt value was measured in the same manner as in Example 22, except that the water-soluble silicon "umo" was not added. This measurement value was used as a control. In other words, this comparative example was a control experiment, and purified water was used as a control.
[0064] [Bacteriostatic effect of silicon] (Example 23) Water-soluble silicon "umo" was added to distilled water and mixed to prepare an aqueous solution with a concentration of water-soluble silicon "umo" of 1% by mass. 5 E. coli was inoculated and the number of E. coli was confirmed 60 minutes later.
[0065] Comparative Example 11 In distilled water, 6.0 x 10 5 E. coli was inoculated and the number of E. coli was confirmed 60 minutes later.
[0066] Example 24 A pH adjuster was added to the water-soluble silicon "umo" to adjust the pH of the water-soluble silicon "umo" to 3.5. Then, 5.6 × 10 5 E. coli was inoculated and the number of E. coli was confirmed 60 minutes later.
[0067] Comparative Example 12 In distilled water, 5.6 x 10 5 E. coli was inoculated and the number of E. coli was confirmed 60 minutes later.
[0068] (Example 25) A pH adjuster was added to the water-soluble silicon "umo" to adjust the pH of the water-soluble silicon "umo" to 3.5. Then, 3.0 × 10 6 Legionella bacteria were inoculated and the number of Legionella bacteria was confirmed 60 minutes later.
[0069] Comparative Example 13 In distilled water, 3.0 x 10 6 Legionella bacteria were inoculated and the number of Legionella bacteria was confirmed 60 minutes later.
[0070] The results obtained are explained below.
[0071] Table 1 and FIG. 1 show the experimental results of Examples 1 to 3 and Comparative Example 1, and also show the measurement results of the elastase activity rate of silicon. Specifically, Table 1 and FIG. 1 show the average and standard deviation of the elastase activity rate of the test substances when the elastase activity rate of the control is set to 100%.
[0072] [Table 1]
[0073] As shown in Table 1 and Figure 1, when a test substance with a concentration of water-soluble silicon "umo" of 3 mass% was used (corresponding to Example 1), the average elastase activity rate was 57.8%. When a test substance with a concentration of water-soluble silicon "umo" of 30 mass% was used (corresponding to Example 2), the average elastase activity rate was 46.0%. Furthermore, when ultrapure water was not added to the water-soluble silicon "umo" and water-soluble silicon "umo" with a concentration of 100% was used (corresponding to Example 3), the average elastase activity rate was 41.3%. These results confirmed that silicon inhibits the activity of elastase.
[0074] Table 2 and FIG. 2 show the experimental results of Example 4 and Comparative Example 2, and show the change in wrinkle area of the skin when the water-soluble silicon "umo" was applied to a skin replica.
[0075] [Table 2] * Tested with undiluted solution
[0076] As shown in Table 2 and Figure 2, the area of wrinkles on the skin was reduced after application of the water-soluble silicon "umo" compared to before application of the water-soluble silicon "umo".
[0077] Table 3 and FIG. 3 show the experimental results of Example 5 and Comparative Example 3, and show the change in the amount of water evaporation from the skin when the water-soluble silicon "umo" was applied to human skin.
[0078] [Table 3] * Tested with undiluted solution
[0079] As shown in Table 3 and Figure 3, when water-soluble silicon "umo" was applied to the skin, the amount of water evaporation from the skin was reduced at all times compared to when water-soluble silicon "umo" was not applied to the skin.
[0080] Table 4 and FIG. 4 show the experimental results of Examples 6 to 8 and Comparative Example 4, and show the change in the production rate of hyaluronic acid when water-soluble silicon "umo" was added to a medium containing fibroblasts. Specifically, Table 4 and FIG. 4 show the average and standard deviation of the elastase activity rate of silicon when the control hyaluronic acid production rate measured in Comparative Example 4 is taken as 100%.
[0081] [Table 4]
[0082] As shown in Table 4 and Figure 4, when an aqueous solution containing water-soluble silicon "umo" at a concentration of 0.01% by mass was added to the culture medium (corresponding to Example 6), the average production rate of hyaluronic acid was 124.3%. When an aqueous solution containing water-soluble silicon "umo" at a concentration of 0.1% by mass was added to the culture medium (corresponding to Example 7), the average production rate of hyaluronic acid was 113.6%. When an aqueous solution containing water-soluble silicon "umo" at a concentration of 1% by mass was added to the culture medium (corresponding to Example 8), the average production rate of hyaluronic acid was 107.0%. These results confirmed that silicon increases the production rate of hyaluronic acid.
[0083] Table 5 and FIG. 5 show the experimental results of Examples 9 and 10 and Comparative Example 5, and show the changes in the expression level of collagen decomposition enzyme 1 gene (MMP1). Specifically, Table 5 and Figure 5 show the average and standard deviation of the expression levels of MMP1 measured in Examples 9 and 10, when the expression level of the control collagen degrading enzyme 1 gene (MMP1) measured in Comparison Example 5 was set to 1.00 ± 0.04.
[0084] [Table 5]
[0085] As shown in Table 5 and Figure 5, when the concentration of water-soluble silicon "umo" was 0.01 mass% (corresponding to Example 9), the average expression level of collagen decomposition enzyme 1 gene (MMP1) was 0.92 ± 0.04. When the concentration of water-soluble silicon "umo" was 0.03 mass% (corresponding to Example 10), the average expression level of collagen decomposition enzyme 1 gene (MMP1) was 0.89 ± 0.04. From these results, it was confirmed that silicon reduces the expression level of collagen decomposition enzyme 1 gene (MMP1).
[0086] Table 6 and FIG. 6 show the experimental results of Examples 11 to 13 and Comparative Example 6, and show the changes in the expression level of hyaluronic acid synthase 2 gene (HAS2). Specifically, Table 6 and Figure 6 show the average and standard deviation of HAS2 measured in Examples 11 to 13, when the expression level of the control hyaluronic acid synthase 2 gene (HAS2) measured in Comparative Example 6 was set to 1.00 ± 0.03.
[0087] [Table 6]
[0088] As shown in Table 6 and Figure 6, when the concentration of water-soluble silicon "umo" was 0.01% by mass (corresponding to Example 11), the average expression level of hyaluronic acid synthase 2 gene (HAS2) was 1.12 ± 0.06. When the concentration of water-soluble silicon "umo" was 0.03% by mass (corresponding to Example 12), the average expression level of hyaluronic acid synthase 2 gene (HAS2) was 1.11 ± 0.02. When the concentration of water-soluble silicon "umo" was 0.1% by mass (corresponding to Example 13), the average expression level of hyaluronic acid synthase 2 gene (HAS2) was 1.33 ± 0.06. These results confirmed that silicon increases the expression level of the hyaluronic acid synthase 2 gene (HAS2).
[0089] Table 7 and FIG. 7 show the experimental results of Examples 14 to 16 and Comparative Example 7, and show the changes in the expression level of hyaluronic acid synthase 3 gene (HAS3). Specifically, Table 7 and Figure 7 show the average and standard deviation of HAS3 measured in Examples 14 to 16, when the expression level of the control hyaluronic acid synthase 3 gene (HAS3) measured in Comparative Example 7 was set to 1.00 ± 0.10.
[0090] [Table 7]
[0091] As shown in Table 7 and Figure 7, when the concentration of water-soluble silicon "umo" was 0.01% by mass (corresponding to Example 14), the average expression level of hyaluronic acid synthase 3 gene (HAS3) was 1.09 ± 0.08. When the concentration of water-soluble silicon "umo" was 0.03% by mass (corresponding to Example 15), the average expression level of hyaluronic acid synthase 3 gene (HAS3) was 1.06 ± 0.08. When the concentration of water-soluble silicon "umo" was 0.1% by mass (corresponding to Example 16), the average expression level of hyaluronic acid synthase 3 gene (HAS3) was 1.36 ± 0.22. These results confirmed that silicon increases the expression level of the hyaluronic acid synthase 3 gene (HAS3).
[0092] Table 8 and FIG. 8 show the experimental results of Examples 17 to 19 and Comparative Example 8, and indicate the changes in the expression level of the β-glucocerebrosidase gene (GBA). Specifically, Table 8 and FIG. 8 show the average and standard deviation of GBA measured in Examples 17 to 19, when the expression level of control GBA measured in Comparative Example 8 was taken as 1.00±0.06.
[0093] [Table 8]
[0094] As shown in Table 8 and Figure 8, when the concentration of water-soluble silicon "umo" was 0.01 mass% (corresponding to Example 17), the average expression level of the β-glucocerebrosidase gene (GBA) was 1.09 ± 0.13. When the concentration of water-soluble silicon "umo" was 0.03 mass% aqueous solution (corresponding to Example 18), the average expression level of the β-glucocerebrosidase gene (GBA) was 1.17 ± 0.04. When the concentration of water-soluble silicon "umo" was 0.1 mass% (corresponding to Example 19), the average expression level of the β-glucocerebrosidase gene (GBA) was 1.27 ± 0.11. These results confirmed that silicon increases the expression level of the β-glucocerebrosidase gene (GBA).
[0095] Table 9 and FIG. 9 show the experimental results of Examples 20 and 21 and Comparative Example 9, and show the changes in the expression level of the profilaggrin gene (FLG). Specifically, Table 9 and FIG. 9 show the average and standard deviation of FLG measured in Examples 20 and 21 when the expression level of control FLG measured in Comparative Example 9 was set to 1.00±0.04.
[0096] [Table 9]
[0097] 9, when the concentration of water-soluble silicon "umo" was 0.01% by mass (corresponding to Example 20), the average value of the profilaggrin gene (FLG) expression level was 1.20±0.05. When the concentration of water-soluble silicon "umo" was 0.03% by mass (corresponding to Example 21), the average value of the profilaggrin gene (FLG) expression level was 1.02±0.12. These results confirmed that silicon increases the expression level of the profilaggrin gene (FLG).
[0098] Table 10 and FIG. 10 show the experimental results of Example 22 and Comparative Example 10, and show the changes in the expression level of transglutaminase 1 gene (TGM1). Specifically, Table 10 and FIG. 10 show the average and standard deviation of TGM1 measured in Example 22, when the expression level of TGM1 in the control measured in Comparative Example 10 was set to 1.00±0.10.
[0099] [Table 10]
[0100] As shown in Table 10 and FIG. 10, when the concentration of water-soluble silicon "umo" was 0.1 mass % (corresponding to Example 22), the average expression level of transglutaminase 1 gene (TGM1) was 1.16±0.06. These results confirmed that silicon increases the expression level of the transglutaminase 1 gene (TGM1).
[0101] Table 11 shows the measurement results regarding the bacteriostatic effect of silicon.
[0102] [Table 11]
[0103] As shown in Table 11, in a solution with a concentration of 1% by mass of water-soluble silicon "umo", 6.0 × 10 5When E. coli was inoculated (corresponding to Example 23), the number of E. coli after 60 minutes was 6.7 × 10 5 It was. On the other hand, 6.0 × 10 5 When E. coli was inoculated (corresponding to Comparative Example 11), the number of E. coli after 60 minutes was 7.3 × 10 5 It was.
[0104] In addition, the acidic water-soluble silicon "umo" with a pH of 3.5 had a concentration of 5.6 × 10 5 When E. coli was inoculated (corresponding to Example 24), the number of E. coli after 60 minutes was 2.5 × 10 3 It was. On the other hand, in distilled water, 5.6 x 10 5 When E. coli was inoculated (corresponding to Comparative Example 12), the number of E. coli after 60 minutes was 5.4 × 10 5 It was.
[0105] Furthermore, 3.0×10 6 When the number of Legionella bacteria was inoculated (corresponding to Example 25), the number of Legionella bacteria after 60 minutes was less than 100. On the other hand, 3.0 × 10 6 When Legionella bacteria were inoculated (corresponding to Comparative Example 13), the number of Legionella bacteria after 60 minutes was 3.2 × 10 6 It was.
[0106] These results confirmed the bacteriostatic effect of silicon on Escherichia coli and Legionella.
Claims
1. Contains silicon and a pH adjuster, The silicon content is 0.05% by mass or more and less than 100% by mass, The silicon is water-soluble silicon extracted from quartz, It is used to improve skin wrinkles and skin firmness. It is used by applying it to the skin, A composition for preventing skin aging.
2. The silicon content is 0.05% by mass or more and less than 5.0% by mass. The composition for preventing skin aging according to claim 1.
Citation Information
Patent Citations
Collagen metabolism improving agent, cosmetics and bathing medicine
JP1995188036A
Cosmetic material for prevention of aging
JP1997295928A
Silica extracted from chaff
JP2016041645A
Charcoal-containing composition
JP2020068776A
Nutritional supplement, and medicine or food / drink containing the nutritional supplement
JP2020100608A